Study of European eel (Anguilla Anguilla L., 1758) contamination by Anguillicoloides crassus in some Tunisian hydrosystems: its impacts on growth parameters - (:unkn) unknown (My University, 2012)
Information lacks about European eel (Anguilla Anguilla L.) infestation by the nematode Anguillicoloides crassus (Kuwahara, Niimi & Itagaki, 1974) in North African populations, and especially in Tunisia. In order to study the situation of this infestation in Tunisian hydrosystems, we: a) analysed the infestation rate and contamination evolution in the population of Ghar El Melh lagoon and “Ichkeul Lake-oued Tinja” system according to time (month, season, year) and we compared it with the Algerian, Moroccan and European eel populations; b) studied the parasite dynamics and contamination evolution by gender (undifferentiated, male, female) and development stage (elver, yellow, silver); c) and, finally, estimated the impact of this parasite on the vital functions of the eel (growth, condition, GSR, HSR, ISR) during its continental life. For comparison, we used samples of sub-adult eels from Bizerte lagoon and juveniles from Medjerda wadi. Our results showed that the infestation of eel populations in North Africa is relatively recent compared to European populations and that this parasite has evolved considerably since it appeared in Tunisia. However, the values of prevalence, mean intensity and abundance remain low compared to the values found for the eels in Algeria, Morocco and Europe. The infestation is more important in terms of prevalence, mean intensity and abundance in freshwater than in brackish or salt water. The levels of infestation appear to be strongly related to the salinity of the colonized water. We have also seen that the infection affects eels entering freshwater (stage VIA1 and VIA2). The infestation is higher in summer and/or in winter and the most parasitized eels are the undifferentiated and migrant specimens. Finally, we showed that Anguillicoloides crassus had neither influence on length and weight nor on the development of liver, gonads and intestines during continental eel life. The parasite seems to have a direct eff
Keywords: African Research